A hybrid approach to joint spectral radius computation - Mejstrik, Thomas; Reif, Ulrich (Linear algebra and its applications, 2025)
In this paper we propose a new method to determine the joint spectral radius of a finite set of real matrices by verifying that a given family of candidates actually consists of spectrum maximizing products. Our algorithm aims at constructing a finite set-valued tree according to the approach of Möller and Reif using a norm that is constructed in the spirit of the invariant polytope algorithm. This combines the broad range of applicability of the first algorithm with the efficiency of the latter. •Novel approach for joint spectral radius computation.•Algorithm remains rigorous.•Algorithm has more general termination guarantees than classical invariant polytope algorithm.